The predictive value of epicardial fat volume for clinical severity of COVID-19 - Mehmet Akif Erdöl; Fatma Civelek Eser; Abdullah Nabi Aslan; Mehmet Erdoğan; Adalet Altunsoy Aypak; Muhammed Said Beşler; Ayşe Kaya Kalem; Ahmet Göktuğ Ertem; Hatice Rahmet Güner (Revista Portuguesa de Cardiologia, 2022)
Introduction: Epicardial adipose tissue serves as a source of inflammatory cytokines and mediators. Cytokine storm is an important cause of morbidity and mortality in coronavirus disease 2019 (COVID-19). Objectives: To investigate the association between epicardial fat volume (EFV), inflammatory biomarkers and clinical severity of COVID-19. Methods: This retrospective study included 101 patients who were infected with COVID-19. Serum inflammatory biomarkers including C-reactive protein (CRP), interleukin-6 (IL-6), procalcitonin (PCT) and ferritin levels were measured. Computed tomography images were analyzed and semi-automated measurements for EFV were obtained. The primary composite endpoint was admission to the intensive care unit (ICU) or death. Results: The primary composite endpoint occurred in 25.1% (n=26) of patients (mean age 64.8±14.8 years, 14 male). A total of 10 patients died. EFV, CRP, PCT, ferritin and IL-6 levels were significantly higher in ICU patients. Moreover, a positive correlation was determined between EFV and CRP (r: 0.494, p<0.001), PCT (r: 0.287, p=0.005), ferritin (r: 0.265, p=0.01) and IL-6 (r: 0.311, p=0.005). On receiver operating characteristic analysis, patients with EFV >102 cm3 were more likely to have severe complications. In multivariate logistic regression analysis, EFV independently predicted admission to the ICU at a significant level (OR: 1.02, 95% CI: 1.01-1.03, p=0.025). Conclusion: EFV and serum CRP, IL-6, PCT and ferritin levels can effectively assess disease severity and predict the outcome in patients with COVID-19. EFV is an independent predictor of admission to the ICU in hospitalized COVID-19 patients. Resumo: Introdução: O tecido adiposo epicárdico é fonte de citocinas inflamatórias e mediadores. A tempestade de citocinas é uma importante causa de morbilidade e mortalidade na doença coronavírus 2019 (COVID-19). Objetivos: Investigar a associação entre volume adiposo epicárdico (VAE), biomarcadores inflamatórios e gravidade clínica da COVID-19. Métodos: Este estudo retrospetivo incluiu 101 doentes infetados com COVID-19. Foram avaliados biomarcadores inflamatórios séricos, incluindo os níveis de proteína C-reativa (PCR), de interleucina-6 (IL-6), de procalcitonina (PCT) e de ferritina. Foram analisadas imagens de tomografia computorizada (TC) e foram obtidas medições semi-automáticas do VAE. O endpoint primário composto foi a admissão na unidade de cuidados intensivos (UCI) ou morte. Resultados: O endpoint primário ocorreu em 25,1% (n=26) dos doentes (idade média 64,8±14,8 anos, 14 homens). Um total de 10 doentes morreu. Os níveis de VAE, PCR, PCT, ferritina e IL-6 foram significativamente superiores nos doentes internados na UCI. Além disso, verificou-se uma correlação positiva entre o VAE e a PCR (r: 0,494, p<0,001), PCT (r: 0,287, p=0,005), ferritina (r: 0,265, p=0,01) e IL-6 (r: 0,311, p=0,005). Na análise de regressão logistica multivariada, os doentes com VAE>102 cm3 tinham maior probabilidade de ter complicações graves. Conclusão: O VAE e os níveis séricos de PCR, IL-6, PCT e ferritina podem avaliar a gravidade da doença e prever o resultado em doentes com COVID-19. O VAE constitui um fator preditivo na admissão dos doentes hospitalizados com COVID-19 numa UCI.